A Role of Phosphatidylserine in the Function of Recycling Endosomes - Hasegawa, Junya; Uchida, Yasunori; Mukai, Kojiro; Lee, Shoken; Matsudaira, Tatsuyuki; Taguchi, Tomohiko (Frontiers in Cell and Developmental Biology, 2021)
Cells internalize proteins and lipids in the plasma membrane (PM) and solutes in the extracellular space by endocytosis. The removal of PM by endocytosis is constantly balanced by the replenishment of proteins and lipids to PM through recycling pathway. Recycling endosomes (REs) are specific subsets of endosomes. Besides the established role of REs in recycling pathway, recent studies have revealed unanticipated roles of REs in membrane traffic and cell signalling. In this review, we highlight these emerging issues, with a particular focus on phosphatidylserine (PS), a phospholipid that is highly enriched in the cytoplasmic leaflet of RE membranes. We also discuss the pathogenesis of Hermansky Pudlak syndrome type 2 (HPS2) that arises from mutations in the AP3B1 gene, from the point of view of dysregulated RE functions.